DESIGN OF MODIFICATION EQUIPMENT TOOLS INVESTIGATION MAGNETIC RESONANCE CHOLANGIOPANCREATOGRAPHY PEDIATRIC PATIENTS IN HOSPITAL SANTO BORROMEUS BANDUNG - Feni Try Sabdo; Fatimah Fatimah; Darmini Darmini (Jurnal Imejing Diagnostik (JImeD), 2018)
Background : On examination MRCP patient pediatric in Radiology Hospital Santo Borromeus using tools made of PVC. But the use of such aids has a deficiency, ie the size is too large so that there is a distance between objects to be checked with body coils that can reducing value of the signal generated. The purpose of this research is to know the design of equipment tools investigation MRCP pediatric examination, difference of image quality and anatomical information resulting from the use of standard hospital aids and modification aids.Methods : This research is a quantitative research with experimental approach to design of modification aids in water phantom and patient pediatric examination MRCP sequence T2 FRFSE axial. The test was performed on image quality that was statistically analyzed by paired T test using SPSS 22. Beside that, the test was also conducted on anatomy information which was assessed by 2 radiologists with qualitative assessment.Results : The results of this study there are significant differences in SNR between the use of standard hospital aids and modification tools with p value 0.001. CNR differences were also significant between the use of standard hospital aids and modification aids with p value 0.001 (p 0.05).Conclusion : The results of image quality and anatomical information showed the best results in the use of tools modifications.